The Community Empowerment Program Experiences Develop English Literacy Through Storybooks and Storytelling - Khairatunnisa; Annisa Khairir Rizki; Nanda Safitri (Ahmad Dahlan Journal of English Studies, 2026)
This study investigated the use of storybooks and storytelling to develop English literacy among young learners through the Community Empowerment Program (PRODAMAT) conducted in Kampung Sroyo Pundong, Bantul, Yogyakarta.  Storybooks and storytelling are language “ecosystems” where words come to life.  Through rhyme and repetition in stories, children learn to recognize the sounds and rhythm of English sounds and reading comprehension. Utilizing a narrative inquiry design, the researchers collected data through interviews and documentation, specifically teacher-written stories, from four magister students of the English Education Study Program at Ahmad Dahlan University who served as mentors. The data analysis included transcription, coding, and analysis as the trustworthiness based on the narrative frame. The findings reveal that storytelling and storybooks serve as of rhyme and rhythmic repetition serves as a scaffold for phonemic awareness, allowing learners to internalize the prosodic features of English (stress, intonation, and rhythm) implicitly. Despite challenges such as limited initial vocabulary and low student confidence, the program successfully increased student motivation and engagement. Additionally, achieved pedagogical practice, which is the integration of theory and practice, through implementing advanced TEFL concepts for various cultural settings with limited resources.